NAFTA’s trade effects: New evidence with a gravity model - Montenegro, Claudio; Soloaga, Isidro (Estudios de Economía, 2016)
This paper estimates econometrically the impact of NAFTA on US-Mexico and US-third countries (groups of countries) trade flows. Using a traditional gravity- equation framework, we try to see to what extent the bilateral trade flows between the US and different countries differ from a gravity-type specification. By incorporating a series of dummy variables into the specification, we interpret the changes in these dummy variables over time as evidence on whether NAFTA affected the trade patterns. The main conclusion is that NAFTA did not have a significant effect on US trade patterns, neither with Mexico nor with other countries in the world (with the exception of CACM).